Reconfiguring Ignacio Ellacuría’s Symbolic Conception of “the Crucified People”: Jesus, the Suffering Servant, and Abel - Castillo, Daniel P. (Theological studies (Baltimore), 2023)
This article offers an appreciative but critical appraisal of Ignacio Ellacuría’s concept of “the crucified people,” which identifies the oppressed peoples of history with both Jesus and the Suffering Servant. In formulating his concept, Ellacuría does not sufficiently delineate the potential volitional differences between Jesus, the Servant, and the crucified peoples of history. As a result, the symbol of the crucified people can present potentially distorted understandings of the relationship between suffering and redemption, distortions that Ellacuría himself would disavow. After surfacing these concerns, I argue that broadening the symbolic framework of the symbol of the crucified people to include not only Jesus and the Servant but also the figure of Abel can protect against these potential distortions.